2023
DOI: 10.3390/app13032003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Current State of Primary and Secondary Zinc Production—A Review

Abstract: This article presents the history of zinc, its production and demand. The quantity of zinc production, both primary zinc from ores and concentrates, and secondary zinc from scrap and zinc-rich waste, was discussed. A comprehensive economic analysis covers zinc prices in the years 1960–2021. The basic methods of obtaining zinc from ores, including pyrometallurgical (Imperial Smelting Process ISP, Kivcet, Ausmelt) and hydrometallurgical (roasting–leaching–electrowinning RLE, atmospheric direct leaching ADL, Engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The HDG process currently consumes more than 50% of the world’s zinc production, with zinc production steadily increasing. At the same time, natural resources of zinc are estimated at a level that allows to meet the growing demand in about 17 years [ 4 ]. It is therefore necessary to limit the consumption of zinc.…”
Section: Introductionmentioning
confidence: 99%
“…The HDG process currently consumes more than 50% of the world’s zinc production, with zinc production steadily increasing. At the same time, natural resources of zinc are estimated at a level that allows to meet the growing demand in about 17 years [ 4 ]. It is therefore necessary to limit the consumption of zinc.…”
Section: Introductionmentioning
confidence: 99%
“…Mukhopadhyay et al [21] studied the phase relations in CaFeSiO 4 -Fe 2 SiO 4 and found a miscibility gap below approximately 1041 • C. the sinter plant-blast furnace process due to its high thermal efficiency, less feed preparation, and efficient SO2 utilization [16]. Although oxygen pressure leaching has been developed for producing zinc in recent years, pyrometallurgy is still utilized to extract zinc from lead and zinc mixed concentrate [17].…”
Section: Phase Equilibrium Studies At Iron Saturationmentioning
confidence: 99%
“…In Europe, Australia, and the USA, the perception of production sites as "polluting" has led to public pressure on both industries and governments. Production in these countries stagnated, and no major investment in metallurgical infrastructure was observed in 2010-2020 [1,2]. In 2022, energy crisis in Europe lead to several shutdowns.…”
Section: Introductionmentioning
confidence: 99%